2016
DOI: 10.1111/rec.12334
|View full text |Cite
|
Sign up to set email alerts
|

A plant traits approach to managing legacy species during restoration transitions in temperate eucalypt woodlands

Abstract: Degraded communities often contain a subset of the species that comprised the predisturbance community. These represent an important legacy of the predisturbance state, yet restoration treatments may be detrimental to them. This study examined the potential of leaf traits and life form to predict whether restoration treatments can maintain legacy swards of Austrostipa bigeniculata (hereafter Austrostipa) while controlling exotic annuals in temperate eucalypt woodlands. Treatments included carbon addition to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…, Laughlin , Cole et al. ). Moreover, species with desired functional traits may be more phylogenetically related than species with less desirable functional traits, which could assist in the selection of species to use for restoration (Hipp et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Laughlin , Cole et al. ). Moreover, species with desired functional traits may be more phylogenetically related than species with less desirable functional traits, which could assist in the selection of species to use for restoration (Hipp et al.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, assessing the functional traits of dominant and subordinate species in restorations could help practitioners develop appropriate management strategies to promote native species (Sandel et al 2011, Laughlin 2014, Cole et al 2016. Moreover, species with desired functional traits may be more phylogenetically related than species with less desirable functional traits, which could assist in the selection of species to use for restoration .…”
Section: Introductionmentioning
confidence: 99%
“…; Cole et al. ). Our conclusions need to be treated with some caution as the botanical sampling only recorded a maximum of six species per quadrat.…”
Section: Discussionmentioning
confidence: 97%
“…However, an earlier study observed similarly poor recruitment of Poa in C4 Bothriochloa swards, as well as high recruitment of C4 Themeda in these C4 swards . Over the 4 years, Austrostipa species grew vigorously and increased in basal area and abundance in all treatments (Cole et al 2016a). seed predation, relatively small seed size in Poa and Rytidosperma), and our results highlight the need for better methods for reestablishing these C3 grasses in restored woodlands.…”
Section: Native Grass Establishmentmentioning
confidence: 96%
“…This can be achieved by burning prior to seed maturation. Importantly, strategic burning and grazing can also promote the health, vigour and competitiveness of native grass swards (Menke 1992;Zedler 2007;Cole et al 2016a). Similar effects can also be achieved by strategic grazing, although this is less well studied (Doll et al 2011;Cole et al 2016b).…”
Section: Introductionmentioning
confidence: 99%